An Emic, Mixed-Methods Approach to Defining and Measuring Positive Parenting Among Low-Income Black Families. Issue 2 (17th February 2017) - McWayne, Christine M.; Mattis, Jacqueline S.; Green Wright, Linnie E.; Limlingan, Maria Cristina; Harris, Elise
ABSTRACT: Research Findings : This within-group exploratory sequential mixed-methods investigation sought to identify how ethnically diverse, urban-residing, low-income Black families conceptualize positive parenting. During the item development phase 119 primary caregivers from Head Start programs participated in focus groups and interviews. These qualitative data were content analyzed using a 3-stage iterative process that resulted in the development of a final set of 72 items for a paper-and-pencil measure. In the measure validation phase of the study initial construct validity of the 72-item measure was assessed with an independent sample of 665 respondents. Common factor analyses revealed 5 dimensions of positive parenting on the Black Parenting Strengths in Context scale that related in expected ways with other parent self-report measures. Practice or Policy : Black Parenting Strengths in Context dimensions provide initial support for a more nuanced operationalization of positive parenting than currently exists in any single scale for use with this group and hold promise for better honoring the culture- and context-specific parenting goals and practices that low-income Black parents subjectively view as important for producing healthy developmental outcomes for their children.